2014
DOI: 10.1890/es13-00198.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in a warmer world: effects of experimental warming, conspecific density, and herbivory on seedling dynamics

Abstract: Abstract. Many effects of a changing climate for organisms, populations, and ecosystems are already apparent. Less studied are the effects of increases in temperature on species interactions. While warming may potentially alter interactions among species, species interactions may also mediate individual species responses to ongoing climatic change. In this experiment we manipulated temperature in field-based, open-top chambers for three years to examine the relationship between biotic interactions and climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
0
14
2
Order By: Relevance
“…As a result, L. tulipifera can produce large numbers of seedlings in any given year and likely experiences stronger density-dependent mortality than other tree species. In our study, L. tulipifera averaged 11.35 individuals m −2 , substantially lower than the densities of seedlings observed in either Burt et al (2014) or Bell, Freckleton & Lewis (2006) (10–80 or 100–1,000 individuals m −2 , respectively) but similar to densities of P. serotina recorded by Packer & Clay (2000) (1–15 individuals m −2 ). Our results therefore suggest that L. tulipifera is subject to density-dependent mortality even at relatively low seedling densities.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…As a result, L. tulipifera can produce large numbers of seedlings in any given year and likely experiences stronger density-dependent mortality than other tree species. In our study, L. tulipifera averaged 11.35 individuals m −2 , substantially lower than the densities of seedlings observed in either Burt et al (2014) or Bell, Freckleton & Lewis (2006) (10–80 or 100–1,000 individuals m −2 , respectively) but similar to densities of P. serotina recorded by Packer & Clay (2000) (1–15 individuals m −2 ). Our results therefore suggest that L. tulipifera is subject to density-dependent mortality even at relatively low seedling densities.…”
Section: Discussioncontrasting
confidence: 63%
“…Many other temperate tree species, like Quercus spp. or Prunus serotina , are also resistant to herbivory or pathogens unless simultaneously subject to high densities of conspecific neighbors and, as a result, intense intraspecific competition (Packer & Clay, 2000; Bell, Freckleton & Lewis, 2006; Burt et al, 2014). Seedling density is therefore likely an important predictor of herbivore-driven mortality (Paine et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In years with late spring frosts, early budburst can damage leaf tissues and erase any carbon gains due to longer growing seasons (Augspurger, 2009(Augspurger, , 2013. Many other factors can potentially interact with phenology to limit increases in carbon sequestration of forests in the future, such as drought, herbivory, heat stress, or disease (Taylor & Whitelaw, 2001;Burt et al, 2014).…”
Section: Warming Effects On Leaf Senescence and Growing Season Lengthmentioning
confidence: 99%
“…Species with different functional types or growth strategies may respond differently to warmed conditions (Burt, Dunn, Nichols, & Sanders, ; Post, ; Post & Pedersen, ). We found that warming increased the growth rate of Salix but decreased the growth rate of Carex .…”
Section: Discussionmentioning
confidence: 99%